(untitled) (World Bulletin of Social Sciences, 2025)
The development of computing machines has fundamentally transformed many aspects of human life and played a decisive role in shaping the digital economy. Digital market relations have become a central element of the global economy, driven by the rapid advancement of information technologies and modern economic interactions. Technological progress serves as a catalyst for economic growth, generating new forms and structures of activity, which provides clear evidence of its impact. This article explores the historical stages of computing technology, the fundamental principles of digital technologies and information and communication systems, as well as the types of computers and their impact on the digital economy. Special attention is given to the significance of computing technologies in areas such as Big Data analytics, financial technologies (fintech), digital services, and cybersecurity. Based on collected data, analytical results, and comparative insights, the article highlights the importance of computing technologies in the expansion of Uzbekistan’s digital economy